Did we do everything we could have? Nurses' contributions to medicines optimization: A mixed‐methods study - Vera Logan; Sarah Keeley; Kevin Akerman; Elyne De Baetselier; Tinne Dilles; Nia Griffin; Lisa Matthews; Bart Van Rompaey; Sue Jordan (Wiley, 2021)
Abstract Aim To explore UK professionals' interpretations of medicines optimization and expansion of nurses' roles. Design This mixed‐methods study sought professionals' views on nurses' involvement, competency and engagement in monitoring patients for adverse effects of medicines, monitoring adherence, prescribing and patient education. Method An online survey and interviews were undertaken with nurses, doctors and pharmacists in Wales and England, May 2018 to July 2019. Results In all, 220 nurses, 17 doctors and 62 pharmacists responded to the online survey, and 24 professionals were interviewed. Nurses were divided over extending their roles, with 123/220 (55.9%) wishing to extend roles in monitoring patients for possible adverse drug reactions (ADRs), 111/220 (50.5%) in adherence monitoring, 121/220 (55.0%) in prescribing and 122/220 (55.4%) in patient education. The best‐qualified nurses were the most willing to increase involvement in monitoring patients for ADRs (aOR 13.00, 1.56-108.01). Interviews revealed that both nurses and doctors assumed the other profession was undertaking this monitoring. Respondents agreed that increasing nurses' involvement in medicines optimization would improve patient care, but expressed reservations about nurses' competencies. Collaboration between nurses and doctors was suboptimal (rated 7/10 at best) and between nurses and pharmacists even more so (6/10 at best). Conclusion Juxtaposition of datasets identified problems with medicines optimization: although most respondents agreed that increasing nurses' involvement would positively impact practice, their educational preparation was a barrier. Only ~50% of nurses were willing to expand their roles to fill the hiatus in care identified and ensure that at least one profession was taking responsibility for ADR monitoring. Impact To improve multiprofessional team working and promote patient safety, nurse leaders should ensure patients are monitored for possible ADRs by at least one profession. Initiatives expanding nurses' roles in medicines optimization and prescribing might be best targeted towards the more educated nurses, who have multidisciplinary support.